Setting Up Community Health Programmes : a practical manual for use in developing countries - Lankester, Ted. (Oxford : Macmillan Education, 2007)
"A manual on how to start, set up, and manage a community based health care program in both urban and rural settings"--Provided by publisher.
Setting the scene -- Working as partners with the community -- Health awareness and motivation -- Initial tasks -- Learning about the community -- Drawing up plans -- The community health worker -- Setting up a community health clinic -- Improving childhood nutrition -- Setting up a childhood immunisation programme -- Dealing with childhood illnesses -- Setting up a maternal health programme -- Setting up a family planning programme -- Setting up a community TB programme -- A community development approach to AIDS care, prevention and control by Ian Campbell and Alison Rader -- Setting up environmental health improvements -- Using medicines correctly -- Monitoring and evaluating the health programme -- Managing personnel and finance -- Cooperating with others -- How to make a programme sustainable.
Originally published: Oxford : Macmillan Education, c2007.
Includes bibliographical references (p. 412-417) and index (p. 418-425).
Keywords: Community health services -- Developing countries -- Handbooks, manuals, etc; Community health services -- Methods; Community health planning -- Methods; Developing countries